1-Year COMBO stent outcomes stratified by the PARIS bleeding prediction score: From the MASCOT registry. (December 2020) - Chandrasekhar, Jaya; Baber, Usman; Sartori, Samantha; Aquino, Melissa B.; Hájek, Petr; Atzev, Borislav; Hudec, Martin; Kiam Ong, Tiong; Mates, Martin; Borisov, Borislav; Warda, Hazem M.; den Heijer, Peter; et al.
Abstract: Background: The COMBO stent is a biodegradable-polymer sirolimus-eluting stent with endothelial progenitor cell capture technology for faster endothelialization. Objective: We analyzed COMBO stent outcomes in relation to bleeding risk using the PARIS bleeding score. Methods: MASCOT was an international registry of all-comers undergoing attempted COMBO stent implantation. We stratified patients as low bleeding-risk (LBR) for PARIS score ≤ 3 and intermediate-to-high (IHBR) for score > 3 based on baseline age, body mass index, anemia, current smoking, chronic kidney disease and need for triple therapy. Primary endpoint was 1-year target lesion failure (TLF), composite of cardiac death, myocardial infarction (MI) not clearly attributed to a non-target vessel or clinically-driven target lesion revascularization (TLR). Bleeding was adjudicated using the Bleeding Academic Research Consortium (BARC) definition. Dual antiplatelet therapy (DAPT) cessation was independently adjudicated. Results: The study included 56% (n = 1270) LBR and 44% (n = 1009) IHBR patients. Incidence of 1-year TLF was higher in IHBR patients (4.1% vs. 2.6%, p = 0.047) driven by cardiac death (1.7% vs. 0.7%, p = 0.029) with similar rates of MI (1.8% vs. 1.1%, p = 0.17), TLR (1.5% vs. 1.6%, p = 0.89) and definite/ probable stent thrombosis (1.2% vs. 0.6%, p = 0.16). Incidence of 1-year major BARC 3 or 5 bleeding was significantly higher in IHBR patients (2.3% vs. 0.9%, p = 0.0094), as was the incidence of DAPT cessation (29.3% vs. 22.8%, p < 0.01), driven by physician-guided discontinuation. Conclusions: Patients with intermediate-to-high PARIS bleeding risk in the MASCOT registry experienced greater incidence of 1-year TLF, major bleeding and DAPT cessation than LBR patients, without significant differences in stent thrombosis.